The Trishanku nation memory, self, and society in contemporary India - Kumar, Deepak 1952- (Oxford University Press, 2016)
A collection of nine reflective essays on post-independence India. Based on memory, both historical and personal, they provide a critical and truthful account of an average citizen's life and the society.